POLÍTICA HABITACIONAL E DIREITO À CIDADE: UM ESTUDO DO RESIDENCIAL PARQUE IGUAÇU III – CURITIBA-PR - Pires, Valdirene da Rocha (2016)
The Right to the City is a concept presented by the City Statute, Federal Law nº 10.257/2001, regarding the guarantee of access to urban land and to socially produced goods and services, which are inherent in the maintenance of life in the city. Such goods and services relate to housing, environmental sanitation, urban infrastructure, transportation, public services, work and leisure. This work is an effort to analyze the conditions of access to public services, elements of the Right to the City, which are available to families, arising from occupation or risk areas,resettled in Residencial Parque Iguaçu III – Curitiba, a housing project built through a partnership between the Popular Housing Company of Curitiba (COHAB) and the Minha Casa Minha Vida Program. Thus, from assumptions of the qualitative research, a questionnaire to the families was used as data collection instrument,with issues that expound on their perceptions of public services and facilities available to them in the territory and, as well as a bibliographical review on the process of urbanization in Brazil and Curitiba was conducted. After the data analysis, it appears that, on the one hand, the relocation of those families resulted in some improvements to their lives, particularly with regard to housing structure; on the other hand, however, it shows the fragility of the provision of public services to them. In this way the fact that the project has been constructed in a socially and spatially segregated area and the absence of public investments appear as the main causes of the difficulties encountered by families.